Perengkahan Katalitik Limbah Plastik Jenis Polypropylene (PP) Menjadi Bahan Bakar Minyak Menggunakan Katalis Zeolit A - Aldi Okta Priyatna; Zultiniar Zultiniar; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Fly ash (FA) sample derived from Indonesia coal were used as raw material to synthesis A zeolite catalyst. The physicochemical properties of FA and A zeolite were characterized by atomic absorption spectroscopy (AAS) and X-ray diffraction (XRD). Catalytic activity of A zeolite wastested in catalytic cracking of polypropylene plastic waste to obtain biofuel. It was found that the highest yield of biofuel obtained using 1.5% A zeolite catalyst with a temperature of 450oC for 60 minutes is 76.82%. In addition, physical properties of biofuel which are density, caloric value wereobtained 0.78 g/mL and 10.26 cal/g, respectively. For chemical compound, it was found that the most dominant was gasoline and kerosene-diesel with fraction percent of 39.80 and 32.65,respectively.Keywords : A Zeolite, Catalytic Cracking, Fuel, Plastic, Polypropylene